Production of bioethanol from sweet lime peel via a statistically optimized simultaneous saccharification and fermentation process using isolated enzymes. Issue 1 (31st March 2022) - John, Indulekha; Pola, Jishnu; Muthukumar, Karuppan; Thanabalan, Murugesan; Appusamy, Arunagiri
ABSTRACT: The present study is to explore sweet lime peel and to investigate the possibility of isolation of enzymes for bioethanol production. Acid assisted steam pretreatment was employed for sweet lime peel as a pretreatment process in order to release more cellulose for hydrolysis. Cellulose content was increased from 25.4% to 34.8% by steam pretreatment. Cellulase and pectinase enzymes required for the hydrolysis of sweet lime peel were isolated from Aspergillus niger by solid-state fermentation. The activity of the in vitro produced cellulase and pectinase were 1.712 FPU/ml and 3.195 IU/ml, respectively. Simultaneous saccharification and fermentation of pretreated sweet lime peel was carried out using isolated cellulase and pectinase enzymes and Saccharomyces cerevisiae respectively. The optimization of process variables, time, pH and temperature on fermentation efficiency was also investigated using response surface methodology. The maximum fermentation efficiency of 71.73% was attained at pH 5°C and 37°C after 72 h of saccharification and fermentation.